59.3k views
9 votes
(-2,-4)

Oy=(x + 2)² +4
Oy=(x - 2)²-4
Oy=-(x - 2)²-4
Oy=-(x + 2)² - 4

(-2,-4) Oy=(x + 2)² +4 Oy=(x - 2)²-4 Oy=-(x - 2)²-4 Oy=-(x + 2)² - 4-example-1

2 Answers

3 votes

Answer:

y = -(x + 2)² - 4

Explanation:

Vertex form of an equation :

y = a(x - h)² + k

  • Vertex = (h, k)

Substituting the coordinates of the vertex in the equation :

y = (x -(-2))² + (-4)

y = (x + 2)² - 4

y = -(x + 2)² - 4 (as the graph opens downwards)

User Kidmose
by
4.3k points
11 votes

Answer:


\textsf{D)} \quad y=-(x+2)^2-4

Explanation:

Vertex form of a quadratic equation:


y=a(x-h)^2+k

where:


  • (h, k) is the vertex

  • a is some constant
    If
    a > 0, the parabola opens upwards
    If
    a < 0, the parabola opens downwards

From inspection of the graph, the vertex (turning point) is (-2, -4).

Substituting the vertex into the equation:


\implies y=a(x-(-2))^2+(-4)


\implies y=a(x+2)^2-4

As the parabola opens downwards,
a < 0:


\implies y=-a(x+2)^2-4

The curve intercepts the y-axis at (0, -8).

Inputting this into the equation and solving for
a:


\implies -8=-a(0+2)^2-4


\implies -4=-4a


\implies a=1

Therefore, the equation of the graph is:


y=-(x+2)^2-4

User Tikia
by
5.6k points